Deported to death: how drug violence is changing migration on the US-Mexico border - Slack, Jeremy (California series in public anthropology, 2019)
The violence of mobility -- I want to cross with a backpack -- Te van a levantar? they will kidnap you : deportation and mobility on the border -- They torture you to make you lose feeling -- Guarding the river : migrant recruitment into organized crime -- The disappeared, the dead, and the forgotten -- Resistance, resilience, and love : the limits of violence and fear -- "Who can i deport?" : protection from removal in the asylum system -- Conclusions : requiem for the removed.